Developing a Small Business Regulatory System - Miller , Geoff (Journal of Law and Governance, 2009)
Introduction Thank you for inviting me to share my thoughts on what the government is doing to reduce the burden on small business. I also look forward to hearing the other speakers talk about how to make the regulatory system more responsive and relevant to business needs. It is more than a year since the fall of Lehman Brothers and the beginning of the Australian Government’s response to the global financial crisis. Today, the Australian economy is showing encouraging signs of recovery. The Government’s policy responses have been largely responsible for placing Australia in a better position than most countries around the world. The Mid-Year Economic and Fiscal Outlook (MYEFO) (released earlier this month) showed that the economy is performing much better than was forecast in the last Budget — MYEFO shows that Australia is the only advanced economy to have recorded positive growth through the year to June 2009. MYEFO also upgraded the growth forecasts for the following two years with consequental falls in the expected peak unemployment rate. Although this is good news, the GFC has clearly affected, and is continuing to impact on, small business. A number of Australian Chamber of Commerce and Industry surveys have reported large falls in small business confidence and conditions throughout 2008 and early 2009. However, the August ACCI Small Business Survey reports that, while conditions for small business are expected to remain challenging, conditions are stabilising. This good news is supported by the most recent Commonwealth Bank – ACCI Business Expectations Survey, which shows that small, medium and large businesses are expecting business conditions to improve significantly during this quarter. It is true that small businesses succeed or fail on the creativity, ingenuity, innovation and imagination of their owners and staff. It is also true that small businesses are notoriously time poor. When considering ways to improve the regulatory framework for small businesses it is important to weigh up the desire to minimise time spent by businesses on compliance, with maintaining the integrity of the market as a whole. People in my position rely on people like you with the specific knowledge and expertise in small business matters to make sure that reforms are developed which benefit both the small business sector and the wider economy.